[latex] x^{3} - 6x^{2} -4x+24=0[/latex] Только прошу поподробнее.Ответ знаю.

[latex] x^{3} - 6x^{2} -4x+24=0[/latex] Только прошу поподробнее.Ответ знаю.
Гость
Ответ(ы) на вопрос:
Гость
x²(x-6)-4(x-6)=0 (x-6)(x²-4)=0 (x-6)(x-2)(x+2)=0 x-6=0 x=6 x-2=0 x=2 x+2=0 x=-2
Гость
[latex]x^3-6x^2-4x+24=0 \\ (x^3-6x^2)-(4x-24)=0 \\ x^2(x-6)-4(x-6)=0 \\ (x-6)(x^2-4)=0 \\ \\ x-6=0~~~~~~~~~~~~~~~~~~~~~~~~~x^2-4=0 \\ x=6~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~x^2=4 \\ ~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~x=б2[/latex] Ответ:  [latex]б2;~6[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы